Analysis of EF-Hand Proteins in Soybean Genome Suggests Their Potential Roles in Environmental and Nutritional Stress Signaling - Zeng, Houqing; Zhang, Yaxian; Zhang, Xiajun; Pi, Erxu; Zhu, Yiyong (Frontiers in Plant Science, 2017)
Calcium ion (Ca2+) is a universal second messenger that plays a critical role in plant responses to diverse physiological and environmental stimuli. The stimulus-specific signals are perceived and decoded by a series of Ca2+ binding proteins serving as Ca2+ sensors. The majority of Ca2+ sensors possess the EF-hand motif, a helix-loop-helix structure which forms a turn-loop structure. Although EF-hand proteins in model plant such as Arabidopsis have been well described, the identification, classification and the physiological functions of EF-hand-containing proteins from soybean are not systemically reported. In this study, a total of at least 262 genes possibly encoding proteins containing one to six EF-hand motifs were identified in soybean genome. These genes include 6 calmodulins (CaMs), 144 calmodulin-like proteins (CMLs), 15 calcineurin B-like proteins (CBLs), 50 calcium-dependent protein kinases (CDPKs), 13 CDPK-related protein kinases (CRKs), two Ca2+- and CaM-dependent protein kinases (CCaMKs), 17 respiratory burstoxidase homologues (RBOHs), and 15 unclassified EF-hand proteins (UEPs). Most of these genes (87.8%) contain at least one kind of hormonal signaling- and/or stress response-related cis-elements in their -1500 bp promoter regions. Expression analyses by exploring the published microarray and Illumina transcriptome sequencing data revealed that the expression of these EF-hand genes were widely detected in different organs of soybean, and nearly half of the total EF-hand genes were responsive to various environmental or nutritional stresses. Quantitative RT-PCR was used to confirm their responsiveness to several stress treatments. To confirm the Ca2+-binding ability of these EF-hand proteins, four CMLs (CML1, CML13, CML39, CML95) were randomly selected for SDS-PAGE mobility-shift assay in the presence and absence of Ca2+. Results showed that all of them have the ability to bind Ca2+. This study provided the first comprehensive analyses of genes encoding for EF-hand proteins in soybean. Information on the classification, phylogenetic relationships and expression profiles of soybean EF-hand genes in different tissues and under various environmental and nutritional stresses will be helpful for identifying candidates with potential roles in Ca2+ signal-mediated physiological processes including growth and development, plant-microbe interactions and responses to biotic and abiotic stresses.